(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
The purpose of the project is to create a curriculum for teaching fundamental football skills and assess how it affects middle school students’ ability levels. The study looks at the improvement percentage in physical test contributions to skill performance in youth football, the experimental group’s technical performance of fundamental football skills in pre- and post-tests, and the significant difference in shooting and passing skills between the groups, which favors the experimental group. In order to improve their skill and physical capacities, age-specific characteristics were taken into consideration when designing the tests that the researchers used to measure youth football ability levels.